Design of an end-to-end demonstration mission of a Formation-Flying Synthetic Aperture Radar (FF-SAR) based on microsatellites. Issue 11 (1st June 2021) - Grasso, M.; Renga, A.; Fasano, G.; Graziano, M.D.; Grassi, M.; Moccia, A.
Abstract: The paper focuses on space system design aspects related to an end-to-end demonstration mission, aiming at showing the feasibility of a Formation Flying Synthetic Aperture Radar (FF-SAR) with microsatellite class platforms ( 100 kg). Trajectory design approaches that can fulfil payload requirements are addressed to enable selected FF-SAR applications. The exploitation of these applications relies on suitable combinations of FF-SAR techniques like Signal-to-Noise Ratio (SNR) enhancement, High-Resolution Wide Swath (HRWS) SAR imaging, and Coherence Resolution Enhancement (CRE). In this framework, a cluster of 3 micro-satellites, working in X-band, flying in a Low Earth Orbit (LEO) close-formation, has been designed as a candidate end-to-end system demonstration mission. One satellite embarks a Transmitting-Receiving (Tx/Rx) radar, i.e. it is a monostatic SAR. The other two satellites are Receiving-only platforms. Critical design aspects related to spacecraft subsystems and formation-flying analysis are addressed to confirm the technical feasibility of the spaceborne distributed system implementing the FF-SAR principle.